HGCROC2: the front-end readout ASICs for the CMS High Granularity Calorimeter. Issue 1 (1st November 2022) - Bouyjou, F.; Bombardi, G.; Callier, S.; Dinaucourt, P.; Dulucq, F.; El Berni, M.; Guilloux, F.; Idzik, M.; de La Taille, C.; Marchioro, A.; Moron, J.; Raux, L.; et al.
Abstract : The CMS High-Granularity Calorimeter (HGCAL) imposes extremely challenging specifications for the front-end electronics: high dynamic range, low noise, high-precision time information and low power consumption, as well as the need to select and transmit trigger information with a high transverse and longitudinal granularity. HGCROC2 is the second prototype of the readout chip embedding almost all the final functionalities. It has 72 channels of the full analog chain: low noise and high gain preamplifier and shapers, a 10-bit 40 MHz SAR-ADC which provides the charge measurement over the linear range of the preamplifier, after the preamplifier saturation a discriminator and TDC provide the charge information from ToT (200 ns dynamic range and 50 ps binning), and a fast discriminator and TDC provide timing information to 25 ps accuracy. This paper reports on the performance in terms of noise, charge and timing, the DAQ and Trigger paths, as well as results from radiation qualification with total ionizing dose (TID) and heavy ions for single-event effects (SEE).